2017
DOI: 10.1016/j.actamat.2017.02.027
|View full text |Cite
|
Sign up to set email alerts
|

Dislocation cross-slip in fcc solid solution alloys

Abstract: Cross-slip is a fundamental process of screw dislocation motion and plays an important role in the evolution of work hardening and dislocation structuring in metals. Cross-slip has been widely studied in pure FCC metals but rarely in FCC solid solutions. Here, the cross-slip transition path in solid solutions is calculated using atomistic methods for three representative systems of Ni-Al, Cu-Ni and Al-Mg over a range of solute concentrations. Studies using both true random alloys and their corresponding averag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(49 citation statements)
references
References 87 publications
(100 reference statements)
3
46
0
Order By: Relevance
“…We note that a heterogeneous distribution of "local" SFEs may affect the plastic deformation mechanisms, considering the existence of both "weak" and "strong" close-packed atomic planes that is in contrast with conventional crystalline alloys. A similar example can be found in studying the dislocation cross-slip affected by the fluctuations in the spatial solute distribution in random solid solutions(27).The average SFE, isf γ and esf γ in CrCoNi alloys can be quantitatively correlated with the degree of chemical SRO, reflected by the total nonproportional number of local atomic pairs, sum δ ∆ , as shown respectively in Fig. 4B-C.…”
supporting
confidence: 66%
“…We note that a heterogeneous distribution of "local" SFEs may affect the plastic deformation mechanisms, considering the existence of both "weak" and "strong" close-packed atomic planes that is in contrast with conventional crystalline alloys. A similar example can be found in studying the dislocation cross-slip affected by the fluctuations in the spatial solute distribution in random solid solutions(27).The average SFE, isf γ and esf γ in CrCoNi alloys can be quantitatively correlated with the degree of chemical SRO, reflected by the total nonproportional number of local atomic pairs, sum δ ∆ , as shown respectively in Fig. 4B-C.…”
supporting
confidence: 66%
“…Based on these studies, a reduction of the SFE increases the total dislocation density and the flow stress, and promotes the splitting of a dislocation, which leads to the suppression of recombining the dissociated dislocations and annihilating the dislocations by cross-slip [32,38]. The SFE of materials can be controlled by adjusting alloying elements [41]. Several studies have been reported regarding the effect of alloying elements to Ni-based alloys on the magnitude of the SFE.…”
Section: Dislocation Density Storage During Cold Swagingmentioning
confidence: 99%
“…These atomistic strategies have been used to determine the influence of different chemical species, such as hydrogen [23] or solid solution Al atoms in Ni [24], on the energy barrier for cross-slip. More recently, an atomistically based model has been proposed to compute the energy barrier for cross-slip as a function of the type and volume fraction of solute atoms [25,26]. Additionally, Chen et al [27] studied the effect of vacancy clusters on the cross-slip activation energy in pure Ni, employing the free-end nudged elastic band methodology.…”
Section: Introductionmentioning
confidence: 99%